Positioning self and other: building equity literacy in collaboration. (18th November 2021) - Rust, Julie; Wessel‐Powell, Christy
Abstract: Collaborative meaning‐making across difference is often undertaken in pursuit of equity, but too often socially constructed power differentials between collaborators on the basis of social class, race, gender, ability, age or other markers are reified. This article examines the ripples produced by one literacy collaboration that took place across public, private and charter schools, nested within urban, suburban and rural districts, traversing cultural, racial and class boundaries. Specifically, we examine retrospective interview data from youth and teachers reflecting on a collaborative project that asked youth to work together with young people from other schools to compose dramatic performances together. Our findings reveal limitations to equitable outcomes across disparate groups working together, particularly around identity markers like race or neurological difference. After juxtaposing a range of positionalities that youth took up when describing the experience of this field trip after the fact, we suggest a set of equity literacy tools for teachers and researchers interested in facilitating more equitable collaborations.